Research priority setting in emergency care: A scoping review. Issue 6 (12th December 2022) - Crilly, Julia; Huang, Ya‐Ling; Krahe, Michelle; Wilhelms, Daniel; Ekelund, Ulf; Hörlin, Erika; Hayes, Jessica; Keijzers, Gerben
Abstract: Objective: Priority areas for emergency care research are emerging and becoming ever more important. The objectives of this scoping review were to (1) provide a comprehensive overview of published emergency care priority‐setting studies by collating and comparing priority‐setting methodology and (2) describe the resulting research priorities identified. Methods: The Joanna Briggs Institute methodological framework was used. Inclusion criteria were peer‐review articles available in English, published between January 1, 2008 and March 31, 2019 and used 2 or more search terms. Five databases (Scopus, AustHealth, EMBASE, CINAHL, and Ovid MEDLINE) were searched. REporting guideline for PRIority SEtting of health research (REPRISE) criteria were used to assess the quality of evidence of included articles. Results: Forty‐five studies were included. Fourteen themes for emergency care research were considered within 3 overarching research domains: emergency populations (pediatrics, geriatrics), emergency care workforce and processes (nursing, shared decision making, general workforce, and process), and emergency care clinical areas (imaging, falls, pain management, trauma care, substance misuse, infectious diseases, mental health, cardiology, general clinical care). Variation in the reporting of research priority areas was evident. Priority areas to drive the global agenda for emergency care research are limited given the country and professional group‐specific context of existing studies. Conclusion: This comprehensive summary of generated research priorities across emergency care provides insight into current and future research agendas. With the nature of emergency care being inherently broad, future priorities may warrant population (eg, children, geriatrics) or subspecialty (eg, trauma, toxicology, mental health) focus and be derived using a rigorous framework and patient engagement.